Some observations on glass beads composition in Sarawak, Singapore and Peninsula Malaysia - Ramli Zuliskandar, Nik Abd. Rahman Nik Hassan Shuhaimi, Jusoh Adnan, Sauman Yunus (N/A, 2011)
Some observations on glass beads composition in Sarawak, Singapore and Peninsula Malaysia by Ramli Zuliskandar, Nik Abd. Rahman Nik Hassan Shuhaimi, Jusoh Adnan, Sauman Yunus,